The Stability of Gob-Side Entry Retaining in a High-Gas-Risk Mine - Junwen Zhang; Yulin Li (Advances in Civil Engineering)
There are series of problems faced by most of the coal mines in China, ranging from low-coal recovery rate and strained replacement of working faces to gas accumulation in the upper corner of coalfaces. Based on the gob-side entry retaining at the No. 18205 working face in a coal mine in Shanxi Province, theoretical analysis, numerical simulation, and engineering practice were comprehensively used to study the mechanical characteristics of the influence of the width of the filling body beside the roadway and the stability of surrounding rock in a high-gas-risk mine. The rational width of the filling body beside the roadway was determined, and a concrete roadway-side support with a headed reinforcement-integrated strengthening technique was proposed, which have been applied in engineering practice. The stability of the filling body beside the roadway is mainly influenced by the movement of the overlying rock strata, and the stability of the surrounding rock can be improved effectively by rationally determining the width of the filling body beside the roadway. When the width of the roadway-side filling body is 2.5 m, the surrounding rock convergence of the gob-side entry retaining is relatively small at only 5% of the convergence ratio. It has been shown that the figure for roof separation is relatively low, and strata behaviors are relatively alleviated and gas density do not exceed the limit, which are the best results of gob-side entry retaining. The results of this research can provide theoretical guidance for excavation of coal mines with similar geological conditions and have some referential significance to safety and efficient production in coal mines.